Vascular endothelial growth factor inhibitors in the treatment of ovarian cancer - S. V. Khokhlova (Опухоли женской репродуктивной системы)
Angiogenesis plays a large role in the development and spread of a number of tumors particularly in the presence of female reproductive system neoplasms. The high expression of vascular endothelial growth factor (VEGF) was found in both the primary tumor and metasta- ses and ascitic fluid in ovarian cancer (OC). Thus, the use of VEGF blockers may be effective in the treatment of OC. The most studied drug used to treat this nosological entity is bevacizumab, the high efficacy of which has been confirmed even when used as monotherapy in the patients who have received treatment many times.